Congenital pneumonia - Zainudin, Zurina; Kassim, Zainab Jummai; Othman, Norlijah (Georg Thieme Verlag, 2018)
Congenital pneumonia is one of the common causes of respiratory distress at birth, with significant morbidity and mortality in neonates, especially among preterm infants, and particularly in developing countries. The etiological agents are many and vary between the developed and underdeveloped parts of the world. Group B streptococci have been attributed as the most common organisms causing severe pneumonia, particularly in developed countries. Human immunodeficiency virus (HIV) is now an increasing risk in underdeveloped countries such as Zimbabwe. Ureaplasma spp. have been highlighted as an important cause of congenital pneumonia in recent years. Clinical manifestations are often nonspecified, and majority of infections appear within the first 48 hours of life. Establishing the microbial diagnosis of congenital pneumonia is challenging. Molecular diagnosis using polymerase chain reaction has an extremely improved diagnostic yield as compared with other conventional detection methods. However, it is often associated with a high level of contamination and may not be available in most hospitals. Management of congenital pneumonia is multifaceted and the most vital is towards eliminating the possible incriminating agent. This review updates the current knowledge on congenital pneumonia and discusses its etiology, diagnosis, preventive strategies, and management.